2021
DOI: 10.3390/biomedicines9121885
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine in Mechanically Ventilated Rats with Lipopolysaccharide-Induced Acute Respiratory Distress Syndrome: The Effect of Intravenous Dose on Oxidative Damage and Inflammation

Abstract: Treatment of acute respiratory distress syndrome (ARDS) is challenging due to its multifactorial aetiology. The benefit of antioxidant therapy was not consistently demonstrated by previous studies. We evaluated the effect of two different doses of intravenous (i.v.) N-acetylcysteine (NAC) on oxidative stress, inflammation and lung functions in the animal model of severe LPS-induced lung injury requiring mechanical ventilation. Adult Wistar rats with LPS (500 μg/kg; 2.2 mL/kg) were treated with i.v. NAC 10 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…However, it failed to protect the rats against developing pulmonary edema and lethality. A study on a mechanically ventilated rat with lipopolysaccharide-induced ALI reported that a high dose of NAC reduced oxidative damage and inflammatory cell in the histology of the lungs [14]. Other studies also reported that NAC treatment protected against lipopolysaccharide-induced ALI [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it failed to protect the rats against developing pulmonary edema and lethality. A study on a mechanically ventilated rat with lipopolysaccharide-induced ALI reported that a high dose of NAC reduced oxidative damage and inflammatory cell in the histology of the lungs [14]. Other studies also reported that NAC treatment protected against lipopolysaccharide-induced ALI [16].…”
Section: Discussionmentioning
confidence: 99%
“…In group III (NAC + OA) (n = 6), after initial recordings of RR, HR, and BP, N-acetylcysteine (163 mg/kg IP) was injected to record the response of RR, HR, and BP [14]. Five minutes after NAC pretreatment, OA (75 µl IV) was administered in rats, and the response was recorded.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…In an experimental study, Kolomaznik et al . 18 showed benefits of using NAC in rat model of endotoxemia. It was demonstrated by the reduction of inflammatory markers and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…50 μL of Saline or tDONs-R9 (60 nM) were intratracheally administrated to ALI model mice at 3 h post LPS stimulation. Meanwhile, NAC, a clinically used drug for broad-spectrum ROS scavenging, as the positive control, was intravenously injected into ALI model mice at 3 h post LPS stimulation (Figure a). All mice were euthanized, and BALF or the lungs were collected for further analysis at 24 h post LPS stimulation.…”
Section: Therapeutic Potency Of Tdons-r9 In Ali Mouse Modelmentioning
confidence: 99%